Analgesic Activity of Cinnabarinic Acid in Models of Inflammatory and Neuropathic Pain - Notartomaso, Serena; Boccella, Serena; Antenucci, N.; Ricciardi, Flavia; Fazio, Francesco; Liberatore, F.; Scarselli, P.; Scioli, M.; Mascio, Giada; Bruno, V.; Battaglia, Giuseppe; Nicoletti, Ferdinando; et al. (Frontiers in Molecular Neuroscience, 2022)
Cinnabarinic acid (CA) is a trace kynurenine metabolite, which activates both type-4 metabotropic glutamate (mGlu4) and arylic hydrocarbon (Ah) receptors. We examined the action of CA in models of inflammatory and neuropathic pain moving from the evidence that mGlu4 receptors are involved in the regulation of pain thresholds. Systemic administration of low doses of CA (0.125 and 0.25 mg/kg, i.p.) reduced nocifensive behavior in the second phase of the formalin test. CA-induced analgesia was abrogated in mGlu4 receptor knockout mice, but was unaffected by treatment with the Ah receptor antagonist, CH223191 (10 mg/kg, i.p.). Acute injection of low doses of CA (0.25 mg/kg, i.p.) also caused analgesia in mice subjected to constriction injury (CCI) of the sciatic nerve. Electrophysiological recording showed no effect of CA on spinal cord nociceptive neurons and a trend to a lowering effect on the frequency and duration of excitation of the rostral ventromedial medulla (RVM) ON cells in CCI mice. However, local application of CH223191 or the group-III mGlu receptor antagonist, MSOP disclosed a substantial lowering and enhancing effect of CA on both populations of neurons, respectively. When repeatedly administered to CCI mice, CA retained the analgesic activity only when combined with CH223191. Repeated administration of CA plus CH223191 restrained the activity of both spinal nociceptive neurons and RVM ON cells, in full agreement with the analgesic activity. These findings suggest that CA is involved in the regulation of pain transmission, and its overall effect depends on the recruitment of mGlu4 and Ah receptors.